Modeling the micro-indentation of metal matrix composites - Rosenberger, Mario Roberto (2007)
A finite element model is developed to quantify the effect of the depth and diameter of the reinforcement in the hardness number of metal matrix composite. The model includes a spherical indenter pressed against a metal containing one reinforcing particle. The results are validated for the non-reinforced material comparing the results of the simulation with analytical models that calculate the properties of the material using Brinell and Meyer hardness and the load-displacement curve. A simple composite consisting of a ductile matrix containing one hard particle of size 0.25-1 of the indenter size and placed at depths 0.1-0.5 times the indenter radius are assumed. The diameters and depths of the impressions for reinforced and matrix materials are determined for different particle size and positions, and the influence on the hardness number is calculated. An overestimation in hardness of reinforced materials was observed with the values dependant on the position and size of the particle. Maximum overestimations of 15% using visual inspection and of 74% using the Oliver and Pharr technique were found in the reinforced materials. In addition, if the impression diameter is at least twice the diameter of the reinforcement, a maximum error of 5% in hardness is produced. © 2006 Elsevier B.V. All rights reserved.